A LabVIEW-based implementation of real-time underwater acoustic OFDM system - Chen, Jaden; Rong, Yue; Nordholm, Sven; Duncan, Alec; He, Z. (IEEE, 2018)
© 2017 University of Western Australia. The orthogonal frequency-division multiplexing (OFDM) technology receives increasing attention in underwater acoustic (UA) communications. This paper presents a real-time OFDM-based UA communication system, implemented using the National Instruments CompactDAQ device and the LabVIEW software. The system design including both the transmitter and receiver is discussed. The performance of this real-time system is verified through a UA communication experiment conducted recently in a tank. Compared with conventional digital signal processor (DSP)-based design, the proposed implementation simplifies the prototype design and reduces the software development time.